1996
DOI: 10.1172/jci118507
|View full text |Cite
|
Sign up to set email alerts
|

The effect of docosahexaenoic acid on aggression in young adults. A placebo-controlled double-blind study.

Abstract: Abstract41 students took either docosahexaenoic acid (DHA)-rich oil capsules containing 1.5-1.8 grams DHA ր day (17 females and 5 males) or control oil capsules containing 97% soybean oil plus 3% fish oil (12 females and 7 males) for 3 mo in a double-blind fashion. They took a psychological test (P-F Study) and Stroop and dementia-detecting tests at the start and end of the study. The present study started at the end of summer vacation and ended in the middle of mental stress such as final exams. In the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
5
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(145 citation statements)
references
References 14 publications
5
132
5
3
Order By: Relevance
“…n-3 LC-PUFA modulate sympathetic activity. Supplementation of the diet with DHA or fish oil for 3 months prevented young students from developing aggression against others at times of mental stress (preparation of final exams [49] and in another similar study in students submitted to the mental stress of preparing final exams decreased plasma norepinephrine concentrations) [50]. Recently, in collaboration with L. Tappy in Lausanne we observed blunting of activation of sympathetic activity during mental stress after 3 weeks of fish oil supplementation in healthy adults [51].…”
Section: Healthy Subjectsmentioning
confidence: 87%
“…n-3 LC-PUFA modulate sympathetic activity. Supplementation of the diet with DHA or fish oil for 3 months prevented young students from developing aggression against others at times of mental stress (preparation of final exams [49] and in another similar study in students submitted to the mental stress of preparing final exams decreased plasma norepinephrine concentrations) [50]. Recently, in collaboration with L. Tappy in Lausanne we observed blunting of activation of sympathetic activity during mental stress after 3 weeks of fish oil supplementation in healthy adults [51].…”
Section: Healthy Subjectsmentioning
confidence: 87%
“…Of the twelve studies reported, two studies found decreases in aggression following supplementation with E-EPA (124) , or EPA þ DHA compared with placebo (155) , one study found decreases in anger following supplementation with EPA þ DHA þ other n-3PUFA compared with placebo (118) , one study found decreases in tension following supplementation with EPA þ DHA þ other n-3PUFA compared with placebo (159) , and one study found decreases in anti-social behaviour following supplementation with EPA þ DHA þ n-6PUFA þ vitamins þ minerals compared with placebo (160) . Two further studies also found improvements in aggression following supplementation compared with placebo, where aggression increased in the placebo group but remained stable in the group treated with EPA þ DHA (153,156) . Four of the studies report no differences in aggression/irritability between treatment and placebo groups following supplementation (126,155,157,158) , one study reports no differences in hostility between treatment and placebo groups (154) and one study reports no differences in anger between treatment and placebo groups (119) .…”
Section: Trial Evidencementioning
confidence: 89%
“…In a trial among young adults in Japan, DHA supplementation with fish oil capsules prevented extra-aggression at times of mental stress (Hamazaki et al, 1996) and lowered resting plasma norepinephrine concentrations by 31% (Hamazaki et al, 2000). In another trial, a high fish diet intervention as part of a cholesterollowering program resulted in a reduction of aggressive hostility as measured by the Hopkins Symptom Checklist (SCL-90) (Weidner et al, 1992).…”
Section: Discussionmentioning
confidence: 99%